Factors Affecting Stunting among Toddlers: A Case Study in West Nusa Tenggara Province - Fauziah, L.M. (EDP Sciences, 2023)
West Nusa Tenggara Province is one of the regions in Indonesia with high stunting cases. Stunting is influenced by various factors. The purpose of this study is to determine the factors that influence the incidence of stunting for toddlers 0-59 months in West Nusa Tenggara Province. Analysis of factors that influence stunting is seen from the average length of schooling, age of first marriage, poverty, health facilities, and sanitation in an area. Data collection was carried out through literature studies obtained from publications and websites of West Nusa Tenggara government agencies. Data analysis is performed with a simple linear regression test using the SPSS application. The results show that factors such as education level and poverty had a significant effect on stunting cases. Meanwhile, factors such as the age of first marriage, health facilities and access to proper sanitation are not risk factors for the high number of stunting in West Nusa Tenggara Province. These show that in West Nusa Tenggara Province there is a need for increased education, increased community communication, in addition, increased enforcement of rules regarding early marriage and policies that support public health, especially improving nutrition and the environment, need to be carried out. © 2023 EDP Sciences. All rights reserved.